Mesenchymal stem cells derived from low risk acute lymphoblastic leukemia patients promote NK cell antitumor activity. Issue 2 (28th July 2015) - Entrena, Ana; Varas, Alberto; Vázquez, Miriam; Melen, Gustavo J.; Fernández-Sevilla, Lidia M.; García-Castro, Javier; Ramírez, Manuel; Zapata, Agustín G.; Vicente, Ángeles
Highlights: ALL-MSCs at diagnosis promote NK cell antitumoral effector functions in contrast to Healthy-MSCs. Mechanisms underlying ALL-MSC immunostimulatory properties include cytokine secretion and cell-to-cell interaction changes. Immunostimulatory effects of ALL-MSCs are progressively attenuated correlating to a leukemia-free bone marrow. Healthy-MSCs adopt ALL-MSC-like immunomodulatory features when exposed to leukemia cells. MSCs can influence the development of ALL modifying their immunological face to promote an effective immune response. Abstract: Mesenchymal stem cells (MSCs) are key components of the bone marrow microenvironment which contribute to the maintenance of the hematopoietic stem cell niche and exert immunoregulatory functions in innate and adaptive immunity. We analyze the immunobiology of MSCs derived from acute lymphoblastic leukemia (ALL) patients and their impact on NK cell function. In contrast to the inhibitory effects on the immune response exerted by MSCs from healthy donors (Healthy-MSCs), we demonstrate that MSCs derived from low/intermediate risk ALL patients at diagnosis (ALL-MSCs) promote an efficient NK cell response including cytokine production, phenotypic activation and most importantly, cytotoxicity. Longitudinal studies indicate that these immunostimulatory effects of ALL-MSCs are progressively attenuated. Healthy-MSCs adopt ALL-MSC-like immunomodulatory features when exposed to leukemia cells, acquiring the ability to stimulate NK cell antitumor function. The mechanisms underlying to these functional changes of ALL-MSCs include reduced production of soluble inhibitory factors, differential expression of costimulatory and coinhibitory molecules, increased expression of specific TLRs and Notch pathway activation. Collectively our findings indicate that, in response to leukemia cells, ALL-MSCs could mediate a host beneficial immunomodulatory effect by stimulating the antitumor innate immune response.